(untitled) (Applied Biological Research, 2012)
Different populations of Botryodiplodia theobromae causing pear die-back and bark canker in Punjab, India were analyzed for their diversity at molecular level, gene flow and heterogeneity. Molecular diversity was assessed on the basis of allele frequencies of randomly amplified poly morphic DNA (RAPD) primers using POPGENE software. Allele frequency ranged from 0.0 to 1.0 in 3 populations of B. theobromae. Mean genetic diversities within population (HS) varied from 0.25 to 0.80 indicating a high diversity. Molecular diversity across the populations ranged from 0.09 to 0.50 with a mean of 0.39; and differed significantly from mean HS (0.27). Diversity indices of RAPD loci varied from very low (< 0.09) to very high HS values (>0.50) across the populations (GST) with a mean GST of 0.30. Lower GST values of 0.019, 0.036,0.052, 0.074 and 0.097 were observed at S116, S1109, S1120, S1118 and S1110 loci, respectively, depicting high genetic diversity among all the isolates. However, at S111 locus the GST value was 0.80 indicating low diversity in population at this locus. Out of 51 loci 33 showed gene flow (Nm) < 1 indicating high genetic differentiation within the population, while rest with Nm >1 had frequent gene flow across the populations of B. theobromae. Pair-wise comparison (GST) values among all the loci ranged from 0.22 to 0.35 revealing low genetic differentiation among the populations. The observed high molecular diversity (HS) within the population suggested that B. theobromae variability was high in Punjab. The RAPD-based dendrorgam divided isolates into 3 major clusters at 65% similarity coefficient. In general, 20-25% similarity was observed among all the isolates of B. theobromae in Punjab.